Self-management of sick days in young people with type 1 diabetes enhanced by phone support: A qualitative study. Issue 2 (4th May 2019) - Farrell, Kaye; Brunero, Scott; Holmes-Walker, Deborah Jane; Griffiths, Rhonda; Salamonson, Yenna
Abstract : Aims and Objectives: The aim of this paper was to evaluate the impact of phone support on sick day management of young people with type 1 diabetes. Method: Qualitative exploratory study to understand the usage of a phone support service available, 8am to 8.30pm, seven days a week. Inclusion criteria were: (a) young people with type 1 diabetes who attend an age-specific service; (b) experienced acute diabetes crisis. Interviews were coded for themes using QSR NVivo™ Version 11 software. Findings were examined through the theoretical lens of the Health Belief Model. Results: Of 20 eligible individuals, 8 participated in the study. Five avoided emergency presentation by accessing the phone support service; three who did not were admitted for diabetic ketoacidosis. The interviews generated 3 major themes: (a) self-efficacy, (b) cues to action, (c) susceptibility. Conclusion: Enhancing self-efficacy and promoting confidence to seek help early during an acute health crisis enables young people to effectively self-manage and avoid hospitalization.